ANALISIS KONTAMINASI DNA BABI PADA ABON DENGAN PRIMER MITOKONDRIA D-LOOP22 MENGGUNAKAN METODE REAL-TIME POLYMERASE CHAIN REACTION - , Rahmawati Taufiq ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The foods basically made from meat such as shredded meat (abon) is one of the main targets of food forgery in market and pork is frequently used as the mixing material. Such practice is contradictory because Islam in Quran clearly prohibits Islamic community to consume the pork, in views of health aspect due to allergic reaction among peoples highly hipersensitive to pork and of vegetarian life style. To overcome the problem, a method should be developed to specifically detect the target pig DNA among other animals DNA although in a very small content. The analysis was performed by doing the pig DNA amplification using the real time PCR method with primers designed based on the D-loop mitochondrial region of pig, where the primers can amplify the target DNA at 22nd-197th basal orders with the amplicon of 176 pb. The specificity test was done on fresh tissues of pig, cow, chicken, goat and horse) and on the mixed shredded meat of pork: beef (the concentrations of 0.5